Swedish journalist 1994 - Asp, Kent; Weibull, Lennart; Löfgren-Nilsson, Monica (University of Gothenburg, 2014)
In 1989 a survey of journalists, Journalist 1989, was carried out with the purpose to shed light on Swedish journalists' perception of their professional role, work situation and press ethical rules.

Journalist 1994 is a follow-up initiated by a research group at the department of journalism and mass communication at Göteborg university in collaboration with research projects at the department of political science, the paper 'Journalisten' and the Swedish Journalists´ Union. The questionnaire was divided into nine blocks: work and professional role; press ethical rules and professional ethics; media habits; politics and the community; estimation of risks; environment opinion; the paper 'Journalisten'; the Swedish Journalists' Union; and background.

Purpose:

The purpose of the study is to investigate how Swedish journalists perceive themselves and society, their professional role and work situation, the problems related to their code of professional ethics and the developments in the media sector.

1989 genomfördes undersökningen Journalist 1989. Syftet med undersökningen var att få en genomlysning av den svenska journalistkåren vad gäller social sammansättning, synen på den journalistiska yrkesrollen, synen på den egna arbetsplatsens sätt att fungera, synen på medier och journalistik samt synen på press- och yrkesetik.

Journalist 1994 är en uppföljning av vad som hänt under fem år i vissa av dessa frågor. Undersökningen är initierad av en forskargrupp vid institutionen för journalistik i samarbete med forskningsprojekt vid statsvetenskapliga institutionen samt tidningen Journalisten och Svenska Journalistförbundet. Frågeformuläret var indelat i nio sammanhängande frågeblock: arbete och yrkesroll; pressetiska regler och yrkesetik; medievanor; politik och samhälle; hälsorisker; miljö; tidningen Journalisten; Svenska journalistförbundet; samt bakgrundsfrågor.

Syfte:

Undersökningen syftar till att belysa hur svenska journalister ser på sig själva och samhället, sin yrkesroll, arbetssituation och medieutvecklingen.
Journalist 1994
Keywords: mass media; massmedia; occupations; yrken; professional ethics; yrkesetik; journalism; journalistik; occupational life; yrkesliv; professional associations; yrkesföreningar; journalists; journalister; Media; Media; Information society; Informationssamhället; Employment; Sysselsättning; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper